Seed-specific expression of AtWRI1 enhanced the yield of cotton seed oil - Maria Butt; Mahnoor Imran; Tanzeela Rehman; Azeem Intisar; Keith Lindsey; Ghulam Sarwar; Uzma Qaisar (Scientific Reports)
Abstract The WRINKLED1 (WRI1) transcription factor controls carbon flow in plants through regulating the expression of glycolysis and fatty acid biosynthesis genes. The role of Gossypium hirsutum WRINKLED1 (GhWRI1) in seed-oil accumulation still needs to be explored. Multiple sequence alignment of WRI1 proteins confirmed the presence of two conserved AP2 domains. The amino acid sequence of GhWRI1 exhibited 62% homology with AtWRI1 and phylogenetic analysis showed that GhWRI1 and AtWRI1 originated from common ancestors. Comparison of three dimensional structures of AtWRI1 and GhWRI1 indicated the presence of an altered alpha helix on the C-terminus that harbours spore coat protein domain in A. thaliana and other members of Brassicaceae but Kin17 domain in G.hirsutum. In the present study, we constructed a novel gene cassette containing AtWRI1 driven by seed-specific promoter and Tobacco Etch Virus enhancer. The transgenic plantlets of G. hirsutum exhibited 35% enhancement in seed oil content and nearly 4-fold increase in oil-bodies in seed endosperm. GC-MS analysis exhibited additional fatty acids i.e. lauric acid methyl ester, 1-dodecanol, palmitoleic acid, margaric acid, stearic acid, linolenic acid, methyl 9,10-methylene-octadecanoate, methyl 18-methylnonadecanoate, 13-docosenoic acid methyl ester, methyl 20-methyl-heneicosanoate, lignoceric acid in the transformants. This is an important study highlighting the enhancement of seed oil content in cotton by seed-specific expression of AtWRI1.